Investigation of Hematological and Biochemical Effects of Feeding Date in the Early Morning on Empty Stomach vs. after Nutrition on Rabbits - H. A Abdul Ameer; N. F Hassan (Archives of Razi Institute, 2022)
Date seeds have been studied for their possible health advantages as they are employed in various traditional remedies. This study aimed to investigate how date affected hematology, renal, and liver function in rabbits before and after date feeding. In total, 30 rabbits were used in this investigation, and they were divided into two groups (n=15). Group one (G1) was considered the control group and received only a meal without dates for 30 days, and group two (G2) was given date seed extract a about 30 ml/kg b.w. for 30 days. The findings revealed that daily oral administration of date extract resulted in a considerable increase in hemoglobin (Hgb) concentration. It is now recognized as a useful source of natural therapeutic ingredients for a variety of ailments. The study results showed that the oral administration of dates led to a significant increase in Hgb concentration, Hgb indices (MCH, MCV, MCHC, PLT, WBCs, and RBCs) and a significant increase in total protein, alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, creatinine, and blood urea nitrogen levels (P≤0.05). However, there were no significant changes in albumin in G2, compared to G1. Finally, dates may help to increase biochemical and hematological parameters in rabbits.